1994
DOI: 10.1002/ajim.4700250510
|View full text |Cite
|
Sign up to set email alerts
|

Risks of asthma associated with occupations in a community‐based case‐control study

Abstract: The aim of this study was to identify occupational risk groups which might usefully be targeted for occupational asthma surveillance and control, using a community-based case-control approach. Data on previous and current occupations held by subjects were analyzed for 787 adult patients with bronchial asthma and 1591 nonasthmatic patient controls, aged 20-54 years, belonging to the three major races (Chinese, Malays, and Indians) in five outpatient primary care polyclinics. Odds ratios (OR) and 95% confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 5 publications
5
48
2
Order By: Relevance
“…The odds ratio in our study is somewhat higher than found in the aforementioned papers (1)(2)(3). It may be that our exclusion of asthmatics with onset in childhood is one reason.…”
Section: Comment On the Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…The odds ratio in our study is somewhat higher than found in the aforementioned papers (1)(2)(3). It may be that our exclusion of asthmatics with onset in childhood is one reason.…”
Section: Comment On the Resultscontrasting
confidence: 56%
“…However, in recent years, some indications of such an association have been obtained. In a case-referent study from Singapore the odds ratio for asthma was significantly increased for manual workers and service personnel, when compared with nonmanual workers, after adjustment for smoking and other factors (1). Similar results were obtained in a community-based cross-sectional study from China, where a relationship between occupational exposure to dust, gas, or fumes and physician-diagnosed asthma has been reported (2).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…(95% CI = 95% confidence interval, RR 1 = relative risk based on all cases of asthma, RR 2 = relative risk after the exclusion of cases of occupational asthma) (14). A case-referent study from Singapore (787 cases, 1591 referents, aged 20-54 years) reported odds ratios for 9 major occupational groups and 30 of their subcategories according to the national classification of occupations (15). Due to the size of the studies, both used a classification of occupations that was less detailed than the one used by us.…”
Section: Discussionmentioning
confidence: 99%
“…Cleaning products have been identified as an occupational risk for asthma and asthma-like symptoms [Ng et al 1994;Kogevinas et al 1999;Medina-Ramon et al 2003;Zock et al 2001;Le Moual et al 2004;Quirce and Barranco 2010;Labrecque 2012]. In addition, acute respiratory distress syndrome in relation to exposure to cleaning products has been reported [Mapp et al 2000].…”
Section: Cleaning Productsmentioning
confidence: 99%